Faktor-Faktor yang Berpengaruh terhadap PAD Sektor Pariwisata di Kota Pariaman Periode Tahun 2010-2020 - Neng Kamarni; Abdul Karib; Yusrizal Yulius (Universitas Batanghari Jambi, 2022)
The purpose of this study is to analyze the factors that influence local revenue in Pariaman City over the last 10 years. The independent variables used include the number of tourists, the number of tourist objects and GRDP at constant prices. while the dependent variable is the local revenue of Pariaman City. The method in analyzing the data to be used is by means of multiple linear analysis by looking at the influence and relationship between the independent variable and the dependent variable, to see whether or not there is an influence between the number of tourists, the number of tourists, and the variable the amount of gross regional domestic product on the basis of price. constant to local revenue in the tourism sector. The results showed that partially GRDP at constant prices had a positive and significant effect on local revenue in the tourism sector of Pariaman City, while the variable number of tourists and the number of tourist objects did not significantly affect local revenue in the tourism sector of Pariaman City.